Phytochemical profile and in vitro evaluation of extracts from leaves of Drimys brasiliensis (Winteraceae) against bovine and equine herpesviruses - Rafael Martins Parreira & , Isabela Cristina Simoni, Oriana Aparecida Fávero, João Henrique G. Lago, Murillo C. Mecchi, Kaidu Hanashiro Barrosa, Maria Judite Bittencourt Fernandes (Journal of Applied Pharmaceutical Science, 2017)
Drimys brasiliensis Miers (Winteraceae) is an evergreen flowering plant found in the Atlantic Forest and has previously determined to have antifungal, antioxidant, and anti-inflammatory activities. The aim of this research is to describe the phytochemical profile and to evaluate the in vitro antiviral properties of crude extracts from leaves of D. brasiliensis, collected in different periods, against equine and bovine herpesviruses. Hydroalcoholic crude extracts were prepared from fresh leaves, collected bimonthly during one year (from August/2008 to June/2009). Phytochemically, these extracts showed to be composed of flavonoids, quercetrin, astilbin and isoastilbin. The antiviral activity was evaluated by viral cytopathic effect inhibitory assay and cytotoxicity assays were also done. All tested extracts displayed inhibitory effects against bovine herpesvirus without seasonal influence, but there was variation in their effect against equine herpesvirus. The results obtained in this study indicate that the extracts from leaves of D. brasiliensis exhibited significant antiviral activity against animal herpesviruses, indicating their potential for medicinal use.
Keywords: Drimys brasiliensis, flavonoids, antiviral, bovine, equine herpesvirus.